(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. The issue of taxing the population has always been a relevant topic throughout history, as the development of the state and the well-being and comfort of the population must be harmoniously aligned. This scientific study provides a detailed analysis of the necessity of distributing the tax burden fairly when taxing individuals, taking into account their social conditions.